The Development of Google Sites-Based Learning Multimedia to Enhance Students’ Competence in Vocabulary Translation - Maulana, Asep; Ma'suq, Ahmad Tarajjil (Institut Agama Islam Negeri Curup, 2024)
This research aimed to develop web-based learning materials using Google Sites for the Arabic Education Program at UIN KHAS Jember. The necessity of embracing digital transformation in the age of Industry 4.0, driven by rapid advancements in science and technology, is evident. In education, adapting multimedia learning to technological progress is crucial. Google Sites, as an innovative multimedia learning platform in the digital age, utilizes advanced educational technology via internet networks. Challenges and students' low enthusiasm in Tarjamah Fauriyah Indunisiyah Arabiyah course contribute to a decline in literal competence. Consequently, the anticipation revolves around the integration of multimedia learning through web-based platforms with Google Sites will improve both the literal competence in Tarjamah Fauriyah Indunisiyah Arabiyah course and students' enthusiasm for learning. In this research, an assessment was carried out to validate the effectiveness and quality of educational materials and web-based learning media utilizing Google Site within the Tarjamah Fauriyah Indunisiyah Arabiyah course at the Arabic Language Education Department Program at UIN KHAS Jember. This research was classified as developmental research, utilizing the ADDIE model, which comprised five phases: analysis, design, development, implementation, and evaluation. The techniques employed for gathering data encompassed observation, surveys, and assessments. The results indicated high validation scores, with the first media expert rating the content as